Psychological Well-Being of Carers of Children with Type 1 Diabetes: A Comparison with Carers of Children without a Chronic Condition - Thomson, Francesca E.; Bergman, Philip B.; Hay, Margaret (Journal of Social Health and Diabetes, 2018)
Context Caring for a child with a chronic illness requires additional responsibilities and burdens.Aims This research examined psychological well-being of carers of children with type 1 diabetes mellitus (T1DM). A comparison group of carers of children without a chronic condition was included to determine the specific influence T1DM has on carer well-being.Methods This cross-sectional correlational study included a sample of 93 carers of children with T1DM, and 84 comparison carers. Participants were administered the 21-item Depression, Anxiety, and Stress Scale (DASS21), and the Parenting Stress Index Short Form 4th edition via an online questionnaire.Results Multivariate analysis revealed no significant differences between carer groups; additional univariate analyses, however, indicated that carers of children with T1DM scored significantly higher on depression and stress subscales on the DASS21, and recorded elevated anxiety scores.Conclusions Carers of children with T1DM appear to manage parenting stress; however, they may be at increased risk of depression, general stress, and anxiety.
Keywords: type 1 diabetes mellitus; carer psychological well-being; comparison group